Patterns of progression: explaining local variations in HE participation rates. (1st November 2019) - Raven, Neil
With the government funded National Collaborative Outreach Programme focusing on areas in England (known as target wards) where higher education progression is low in absolute terms and lower than expected given prior attainment figures, this article explores the educational trajectories that young people from these localities are likely to take. These trajectories are contrasted with those associated with high progression areas. Two maps that profile these differences are presented. These are initially discussed through a consideration of published sources, which were used to inform their design. The authenticity of what they depict is then assessed through the insights provided by careers and outreach practitioners with experience of working with young people from low progression areas across England. Reflecting on these findings, it is argued that an appreciation of the patterns of progression captured in these maps can contribute to an understanding of the underlying reasons for geographical differentials in higher education participation. It can also inform the kinds of outreach activity likely to be effective at widening local participation rates. Whilst this study focuses on the English context, the discussion should have broader appeal since spatial variations in higher education progression are a widely recognised phenomenon.